2017
DOI: 10.1161/atvbaha.117.309119
|View full text |Cite
|
Sign up to set email alerts
|

Ezetimibe Increases Endogenous Cholesterol Excretion in Humans

Abstract: Objective Ezetimibe improves cardiovascular outcomes when added to optimum statin treatment. It lowers LDL cholesterol and percent intestinal cholesterol absorption, but the exact cardioprotective mechanism is unknown. We tested the hypothesis that the dominant effect of ezetimibe is to increase the reverse transport of cholesterol from rapidly-mixing endogenous cholesterol pool into the stool. Approach and Results In a randomized, placebo-controlled, double-blind parallel trial in 24 healthy subjects with L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 28 publications
0
18
0
1
Order By: Relevance
“…70 These findings are consistent with those of the IMPROVE-IT trial (Improved Reduction of Outcomes: Vytorin Efficacy International Trial) that demonstrated that ezetimibe provided an additional beneficial prognostic effect to statin therapy. 71 Lin et al 72 demonstrated that a 6-week treatment of ezetimibe in a standard dose not only reduced intestinal cholesterol absorption but also promoted reverse cholesterol transport from endogenous cholesterol pools into the stool. Ezetimibe did not affect the plasma concentration of high-density lipoprotein-a beneficial cholesterol with vasoprotective property of enhancing endothelial NO production through activation of eNOS.…”
Section: Novel Therapeutic and Diagnostic Targets Agents For Metabolimentioning
confidence: 99%
See 1 more Smart Citation
“…70 These findings are consistent with those of the IMPROVE-IT trial (Improved Reduction of Outcomes: Vytorin Efficacy International Trial) that demonstrated that ezetimibe provided an additional beneficial prognostic effect to statin therapy. 71 Lin et al 72 demonstrated that a 6-week treatment of ezetimibe in a standard dose not only reduced intestinal cholesterol absorption but also promoted reverse cholesterol transport from endogenous cholesterol pools into the stool. Ezetimibe did not affect the plasma concentration of high-density lipoprotein-a beneficial cholesterol with vasoprotective property of enhancing endothelial NO production through activation of eNOS.…”
Section: Novel Therapeutic and Diagnostic Targets Agents For Metabolimentioning
confidence: 99%
“…Ezetimibe did not affect the plasma concentration of high-density lipoprotein-a beneficial cholesterol with vasoprotective property of enhancing endothelial NO production through activation of eNOS. 72 Denimal et al 73 showed that this beneficial effect of high-density lipoprotein was impaired by the sphingosine-1-phosphate depletion of high-density lipoprotein in patients with metabolic syndrome. On the basis of the premise that targeting glucagon-like peptide (GLP)-1 could provide better treatment of diabetes mellitus via pleiotropic cardiovascular protective effects beyond glycemic control, many clinical trials of GLP-1-based therapies have been conducted with variable effects on cardiovascular outcomes, and others are ongoing.…”
Section: Novel Therapeutic and Diagnostic Targets Agents For Metabolimentioning
confidence: 99%
“…31 This is likely due to inter-individual differences in metabolic regulation rather than analytical error because our previous work shows that repeated FEEC measurements in the same individual have a coefficient of variation of about 10%. 8 …”
Section: Discussionmentioning
confidence: 99%
“…36 Although the result has been attributed to LDL cholesterol lowering, the actual mechanism is unknown and recent work shows that FEEC is increased about 70% by ezetimibe. 8 Further work is needed to establish the utility of treatments directed toward whole body cholesterol metabolism.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation